2008
DOI: 10.1016/j.semcdb.2007.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Congenital cataracts and their molecular genetics

Abstract: Cataract can be defined as any opacity of the crystalline lens. Congenital cataract is particularly serious because it has the potential for inhibiting visual development, resulting in permanent blindness. Inherited cataracts represent a major contribution to congenital cataracts, especially in developed countries. While cataract represents a common end stage of mutations in a potentially large number of genes acting through varied mechanisms in practice most inherited cataracts have been associated with a sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
257
0
17

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(277 citation statements)
references
References 131 publications
3
257
0
17
Order By: Relevance
“…41 Several point mutations in HGD have been linked to congenital cataract formation due to significantly decreased solubility of the protein at body temperature leading to increased light scattering and, eventually, blindness. 37,[40][41][42][43][44] Therefore, LLPS of HGD is a readily quantifiable phase transition through which the effect that the addition of a fluorescent dye, by covalent attachment of an organic fluorophore, can be probed. Additionally, the surface chemistry of HGD ensures that the both the position and number of small molecules conjugated to the protein can be controlled.…”
Section: Introductionmentioning
confidence: 99%
“…41 Several point mutations in HGD have been linked to congenital cataract formation due to significantly decreased solubility of the protein at body temperature leading to increased light scattering and, eventually, blindness. 37,[40][41][42][43][44] Therefore, LLPS of HGD is a readily quantifiable phase transition through which the effect that the addition of a fluorescent dye, by covalent attachment of an organic fluorophore, can be probed. Additionally, the surface chemistry of HGD ensures that the both the position and number of small molecules conjugated to the protein can be controlled.…”
Section: Introductionmentioning
confidence: 99%
“…By comparing the properties of several mutants of HGD in solution with those of the wild type, we have identified specific changes in the homologous (i.e., γ-γ interactions) that led to the formation of distinct condensed phases (6,7) and accounted for the increased light scattering due to these mutations (8)(9)(10)(11)(12)(13). These studies revealed a class of γ-crystallin mutations in which small changes to the protein surface were sufficient to bring about severe solubility changes, without unfolding the protein, and were in direct contrast to other mutations (i.e., other missense mutations, insertions, and splice mutations) that are accompanied by alterations in protein fold and stability (1,14,15).…”
mentioning
confidence: 98%
“…T he vertebrate lens contains three families of constituent proteins, the α-, β-, and γ-crystallins, closely packed such that the total protein concentration in the central region of the lens, i.e., nucleus, exceeds 400 mg∕mL (1). Normally, the close protein packing ensures that short-range order is maintained within the fiber cell, such that fluctuations in the refractive index that cause light scattering are minimized, and the lens is transparent (2,3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This has to be taken into account when one examines available data on the breakdown of pediatric cataract etiology that suggest 10-25% to be genetic in etiology whereas 60% are idiopathic. 6 Within the "genetic" category of pediatric cataract, mutations in crystallins are the most common, accounting for nearly 50% of cases. 7 However, more than 30 loci have been implicated.…”
mentioning
confidence: 99%